Intercultural Human Resource Management Practices And Employees’ Satisfaction In Quoted Food And Beverages Mncs In Nigeria - Arogundade, K. K. (Archives of Business Research, 2021)
This study investigated the impact of intercultural human resource management practices (Training and development; Employee empowerment; and Compensation practices) on employees’ satisfaction in food and beverages MNCs in Nigeria. The study adopted descriptive survey research design. The target population comprises 6,356 staff of quoted food and beverages MNCs in Nigeria. Taro Yamane statistical formulae was used to determine the sample size of 1,568. Purposive sampling technique was used to determine the respondents which included Nigerians and Other Nationals working in the quoted food and beverages MNCs. A structured survey questionnaire was adapted, validated, and used for the construct ranged between 0.61 and 0.93. The response rate to the 1,568 copies of the questionnaire administered was 74%. Data were analysed using descriptive and inferential (Student T-test of multiple regression analysis) statistics. Hypotheses were tested at 0.05 level of significance using SPSS 20. Findings revealed that Training and Development practices, Employee empowerment practice, and Compensation practice had significant positive influence on employees’ satisfaction among Nigerians and Other Nationals in food and beverages MNCs in Nigeria (β = .064 - .526; P< .000 - .021; β = .107 - .312; P< .000) : (β = .168 - .299; P< .000: β = -.15; P> .566; - .225 -.246; P< .000) (β = -.144 -.421; P< .000; β = -.004; P> .886): (β = -.105 - .456; P< .000 -.001): respectively, except for collectivity and individuality that had negative and insignificant influences on employees’ satisfaction among Nigerians with respect to compensation and employee empowerment.